Current Cancer Survivorship Practices, Services and Delivery: A Report from the Children's Oncology Group (COG) Nursing Discipline, Adolescent/Young Adult and Late Effects Committees - Eshelman-Kent, Debra (J Cancer Surviv, 2011)
(1) PURPOSE: To describe survivorship services provided by the Children's Oncology Group (COG), an assessment of services was undertaken. Our overall aim was 1) to describe survivorship services, including the extent of services provided, resources (personnel, philanthropy, research funding), billing practices, and barriers to care and 2) to describe models of care that are in use for childhood cancer survivors and adult survivors of childhood cancer. (2) METHODS: 179 of 220 COG institutions (81%) completed an internet survey. (3) RESULTS: One hundred fifty-five (87%) reported providing survivorship care. Fifty-nine percent of institutions provide care for their pediatric population in specialized late effects programs. For adult survivors, 47% of institutions chose models of care which included transitioning to adult providers for risk-based health care, while 44% of institutions keep survivors indefinitely at the treating institution (Cancer Center Based Model without Community Referral). Sixty-eight percent provide survivors with a copy of their survivorship care plan (SCP). Only 31% of institutions provide a detailed summary of results after each clinic visit, and 41% have a database to track survivor health outcomes. Survivorship care for initial and annual visits is estimated to be minimally 122 and 91 minutes respectively. The most prevalent barriers to care were the lack of dedicated time for program development and a perceived insufficient knowledge on the part of the clinician receiving the transition referral. (4) CONCLUSIONS: Not all COG institutions provide dedicated survivorship care, care plans, or have databases for tracking outcomes. Transitioning to adult providers is occurring within the COG. Survivorship care is time-intensive.